Thread shape affects the stress distribution of torque force on miniscrews: a finite element analysis. Issue 13 (2nd October 2020) - Ye, Yu-shan; Yi, Wei-min; Zhuang, Pei-lin; Liu, Mo; Yu, Yan-song; Lu, Ying-juan; Yao, Qing-he; Wang, Wei; Chang, Shao-hai
Abstract: This study aimed to investigate the effect of miniscrews thread shape on the stress distribution receiving a torque load. Seven thread shapes (S, V1, V2, B1, B2, R1, R2) models were constructed and a 6 Nmm-torque load was applied. The order of maximum equivalent stress (EQV) value was V1 > V2 > B1 > R1 > R2 > B2 > S. The order of maximum displacement of miniscrew (Max DM) value was S > B2 > R1 = V1 > B1 > V2 > R2. Model R2 may be the most appropriate thread shape affording a torque force.